Patogenicidade e expressão do perfil de proteínas por SDS-Page da relação Macrophomina Pseudophaseolina X Cucumis Melo L. - Maia, Vitor Rafael Oliveira (Universidade Federal Rural do Semi-Árido, 2021)
Melon (Cucumis melo L.) culture has great economic importance in the Brazilian semiarid region, due to the favorable conditions for its cultivation. There are many phytosanitary problems found in the culture, such as the diseases caused by root pathogens. A new species of the genus Macrophomina has been identified, Macrophomina pseudophaseolina, which may be associated with weeds present in melon cultivation areas as an alternative host, causing root rot and vine decline (RRVD). The aim of this work was to analyze the pathogenicity and the expression of proteins differentially expressed in accessions of Cucumis melo L. as a function of the response to biotic stress caused by the phytopathogen M. pseudophaseolina. In the first stage, artificial inoculation of the plants was carried out using the toothpick method and pathogenicity analysis. The experiment was carried out in a completely randomized design with a 2x2 + 2 factorial scheme, using two distinct melon accessions, one potentially resistant (Ag- 15591Ghana) and the other susceptible (MR-1) to M. phaseolina; two contrasting isolates of M. pseudophaseolina (CMM4826 more aggressive and CMM4807 less aggressive), plus two control groups. These accessions were used as a parameter because there is no previous resistance information for M. pseudophaseolina. According to the pathogenicity analysis, the present study confirmed the access Ag-15591Ghana as moderately resistant (MR), for both tested isolates, while the MR-1access was classified as highly susceptible (HS) to CMM4826 and susceptible (SU) to CMM4807. In the second stage, the plant samples of stem and root of the access Ag-15591Ghana were collected, after 30 days of the inoculation with M. pseudophaseolina, for protein extraction, perform sodium dodecyl sulfate polyacrylamide gel electrophoresis (SDS-PAGE) in addition to the analysis of the band profile of the different treatments. The presence of differentially expressed bands was observed after inoculation of the seedlings with the two isolates in relation to the control, for both tissues. The number of differentially expressed bands was lower, in stem and root, for the Ag-15591Ghana access when inoculated with the most aggressive isolate CMM4826. These results are important as they may contribute in the future to crop breeding programs and the development of effective control measures, based on resistant cultivars
Keywords: Proteômica; Fitopatógeno; Cucurbitaceae; Proteomic; Phytopathogen; Cucurbitaceae; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA